2021
DOI: 10.3390/ijms22136905
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia as a Stimulus for the Maturation of Meniscal Cells: Highway to Novel Tissue Engineering Strategies?

Abstract: The meniscus possesses low self-healing properties. A perfect regenerative technique for this tissue has not yet been developed. This work aims to evaluate the role of hypoxia in meniscal development in vitro. Menisci from neonatal pigs (day 0) were harvested and cultured under two different atmospheric conditions: hypoxia (1% O2) and normoxia (21% O2) for up to 14 days. Samples were analysed at 0, 7 and 14 days by histochemical (Safranin-O staining), immunofluorescence and RT-PCR (in both methods for SOX-9, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…In normoxia, cell death and hypertrophic phenomena were more pronounced. These findings differ from recent evidence, where the study of the entire tissue showed an onset of extracellular matrix production after 14 days of culture [38]. To explain these apparent conflicting data, we have to consider that the tissue cultured in the two experiments had different dimensions, and in the present study the smaller dimensions probably allowed for a better perfusion of the culture medium.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In normoxia, cell death and hypertrophic phenomena were more pronounced. These findings differ from recent evidence, where the study of the entire tissue showed an onset of extracellular matrix production after 14 days of culture [38]. To explain these apparent conflicting data, we have to consider that the tissue cultured in the two experiments had different dimensions, and in the present study the smaller dimensions probably allowed for a better perfusion of the culture medium.…”
Section: Discussioncontrasting
confidence: 92%
“…Thus, hypoxia can be used as a stimulus to overcome the problem related to the de-differentiation in human meniscal cells [44], and it can be applied to promote the maturation of neonatal piglet meniscal cells [38]. Furthermore, it has been observed that the change in cell phenotype coincides with a change in the vascularity of the tissue in the meniscus [29,45]; therefore, in this study we focused our attention on two particular vascular factors, the pro-angiogenic factor CD31 and the anti-angiogenic factor endostatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen I, the major component of the meniscus fibrocartilage's ECM, served as a reference biomaterial. Hypoxia was used since it has been proven as a stimulus for the maturation of meniscus fibrochondrocytes (Herrera Millar et al, 2021). Our previous research has found that hypoxia and TGF-β3 synergistically mediated the inner meniscus-like tissue matrix formation (Szojka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%